Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 36

Answer

x =$\frac{1}{2}$ y = 3

Work Step by Step

x = $\frac{5}{6}$y -2 12x - 5y = -9 substitude x to the second equation 12( $\frac{5}{6}$y - 2 ) - 5y = -9 10y - 24 - 5y = -9 5y = 15 y = 3 substitude y = 3 to first equation x = $\frac{5}{6}$(3) -2 x = $\frac{5}{2}$ - $\frac{4}{2}$ x = $\frac{1}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.